Assessing the Language Abilities of Bahamian Creole English--Speaking Children. - Moss, Danielle; Timler, Geralyn R. (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: Speech-language pathologists (SLPs) assessing the expressive language of dual language learners may encounter challenges in making clinical judgments of language difference, developmental errors (e.g., overgeneralization), and language disorder. The purpose of this tutorial is to provide SLPs with language assessment information for children of Bahamian descent who speak Bahamian Creole English and English. Method: Using three cases as examples, we propose and describe a contextualized assessment approach. With this approach, we use multiple pieces of assessment data and place a child in a basic framework to ascertain what the context requires the child to do and what the child is currently doing and also determine how to support the child's language development. Results: The tutorial highlights the core components of the assessment process (i.e., referral, case history, assessment, and diagnosis). Guidelines for treatment are also addressed. Conclusions: Potential issues that can arise during the assessment of the language development of Bahamian children are addressed using a contextualized assessment approach. Assessment resources are provided within this tutorial.